2014
DOI: 10.1088/0957-0233/25/12/125105
|View full text |Cite
|
Sign up to set email alerts
|

Reduced length fibre Bragg gratings for high frequency acoustic sensing

Abstract: In-fibre Bragg gratings (FBGs) are now well established for applications in acoustic sensing. The upper frequency response limit of the Bragg grating is determined by its gauge length, which has typically been limited to about 1 mm for commercially available Type 1 gratings. This paper investigates the effect of FBG gauge length on frequency response for sensing of acoustic waves. The investigation shows that the ratio of wavelength to FBG length must be at least 8.8 in order to reliably resolve the strain res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Non-destructive damage/defect detection based on high-frequency acoustic sensing requires the use of 200-300 μm-long low-loss Type I FBGs to probe the radiating elastic wave field. The wavelength of the elastic wave field has to be appreciably larger than the gauge length of the FBG to avoid a non-uniform strain along the FBG, which will result in an irregular reflection spectrum [4].…”
Section: Type I Very Short Fbgs For High-frequency Acoustic Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-destructive damage/defect detection based on high-frequency acoustic sensing requires the use of 200-300 μm-long low-loss Type I FBGs to probe the radiating elastic wave field. The wavelength of the elastic wave field has to be appreciably larger than the gauge length of the FBG to avoid a non-uniform strain along the FBG, which will result in an irregular reflection spectrum [4].…”
Section: Type I Very Short Fbgs For High-frequency Acoustic Sensingmentioning
confidence: 99%
“…6(c), indicates that annealing for 24 hours at 150 °C not only will give long term stability to the grating for room temperature operation but will also make it quasi-stable at 150 °C. Type I gratings written through the protective polyimide coatings of single mode fibers have been shown to have mechanical reliability approaching that of the pristine fiber [14], making these very short gratings suitable for acoustic-based structural health monitoring where the strain fields approach 50,000 microstrains [4] in amplitude.…”
Section: Type I Very Short Fbgs For High-frequency Acoustic Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical fiber sensors are not only more durable than piezo-ceramic sensors but are also immune to electromagnetic interference, have a small footprint which allows them to be easily embedded in fiber composites, and in the case of FBGs are readily multiplexed allowing for distributed sensing. Recent studies have shown that FBG sensors can achieve high bandwidths and are thus capable of detecting higher order Lamb waves [ 6 ] and when written in a high-density array are capable of resolving multi-modal wave packets into constituent modes [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Culshaw et al [1] demonstrated that FBG grating length shorter than 1/6 of signal wavelength is desired to maximize the signal transfer from the substrate to the FBG. In addition to changing the grating length, Davis et al [2] varied the ultrasonic wave frequency to change the wavelength to FBG grating length ratio, showing that shorter grating length can resolve higher frequency (i.e., shorter wavelength) signals without reduction in signal amplitude.…”
Section: Introductionmentioning
confidence: 99%